Influencers ecuatorianos y su marca personal. - Zhapan Revilla, Geovanny Fernando (My University, 2019)
The present work used a qualitative method to analyze the behavior pattern of Ecuadorian influencers in order to understand their personal brand positioning in the country, which has been considered as a case study. The objective was to identify how Ecuadorian influencers have used social networks as a means of communication to position their personal brand. The results indicate that the majority of influencers that were taken into account for this study use (comic) entertainment as a method of capturing the attention of their followers and increasing their local reach nationwide. It concludes with a panoramic perspective of the tool that influencers use to place themselves in a place where their personal brand can be seen and also their behavior pattern, more information about this is provided, in the development of the detailed article with a classification of object of study and the results found.
El‌ ‌presente‌ ‌trabajo‌ ‌usó‌ ‌un‌ ‌método‌ ‌cualitativo‌ ‌para‌ ‌analizar‌ ‌el‌ ‌patrón‌ ‌de‌ ‌comportamiento‌ ‌de‌ los‌ ‌influencers‌ ‌ecuatorianos‌ ‌con‌ ‌el‌ ‌fin‌ ‌de‌ ‌entender‌ ‌su‌ ‌posicionamiento‌ ‌de‌ ‌marca‌ ‌personal‌ ‌en‌ el‌ ‌país,‌ ‌lo‌ ‌cual‌ ‌ha‌ ‌sido‌ ‌considerado‌ ‌como‌ ‌un‌ ‌caso‌ ‌de‌ ‌estudio.‌ ‌El‌ ‌objetivo‌ ‌que‌ ‌se‌ ‌planteó‌ ‌fue‌ ‌identificar‌ ‌cómo‌ ‌los‌ ‌‌influencers‌‌ ‌ecuatorianos‌ ‌han‌ ‌usado‌ ‌las‌ ‌redes‌ ‌sociales‌ ‌como‌ ‌medio‌ ‌de‌ ‌comunicación‌ ‌para‌ ‌posicionar‌ ‌su‌ ‌marca‌ ‌personal.‌ ‌Los‌ ‌resultados‌ ‌indican‌ ‌que‌ ‌la‌ ‌mayoría‌ ‌de‌ ‌influencers‌ ‌‌que‌ ‌se‌ ‌tomaron‌ ‌en‌ ‌cuenta‌ ‌para‌ ‌este‌ ‌estudio‌ ‌usan‌ ‌el‌ ‌entretenimiento‌ ‌(cómico)‌ ‌como‌ ‌método‌ ‌de‌ ‌captar‌ ‌la‌ ‌atención‌ ‌de‌ ‌sus‌ ‌seguidores‌ ‌y‌ ‌aumentar‌ ‌su‌ ‌alcance‌ ‌local‌ ‌a‌ ‌nivel‌ ‌nacional.‌ ‌Se‌ ‌concluye‌ ‌con‌ ‌una‌ ‌perspectiva‌ ‌panorámica‌ ‌de‌ ‌la‌ ‌herramienta‌ ‌que‌ ‌utilizan‌ ‌los‌ ‌influencers‌ ‌para‌ ‌colocarse‌ ‌en‌ ‌un‌ ‌sitio‌ ‌donde‌ ‌su‌ ‌marca‌ ‌personal‌ ‌pueda‌ ‌ser‌ ‌vista‌ ‌y‌ ‌así‌ ‌mismo‌ ‌su‌ ‌patrón‌ ‌de‌ ‌comportamiento,‌ ‌se‌ ‌proporciona‌ ‌más‌ ‌información‌ ‌de‌ ‌esto,‌ ‌en‌ ‌el‌ ‌desarrollo‌ ‌del‌ ‌artículo‌ ‌detallado‌ ‌con‌ ‌una‌ ‌clasificación‌ ‌del‌ ‌objeto‌ ‌de‌ ‌estudio‌ ‌y‌ ‌los‌ ‌resultados‌ ‌encontrados.‌ ‌
Keywords: INFLUENCERS; REDES SOCIALES; MARCA PERSONAL; CONTENIDO NO COMERCIAL